PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Fitri Siti Sundari; Elis Indrayani (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
APPLICATION OF GUIDED INQUIRY LEARNING MODELS TO IMPROVE MATHEMATICAL LEARNING OUTCOMESAbstract.  The purpose of this study was to determine the Implementation of Guided Inquiry Learning Models to Improve Mathematics Learning Outcomes. The subjects of this study were fifth grade students of Lawanggintung I Elementary School, Bogor City consisting of 36 students with a composition of 20 male students and 16 female students. This research was a class action research carried out collaboratively by two cycles. The study was conducted in the odd semester of the 2019-2020 school year. This class action research was conducted in 2 cycles, in cycle one, and cycle two consisted of four main actions namely planning, implementing actions, observing, and reflecting. The results of this study indicate the assessment of the implementation of learning in the first cycle of 72.9 and 85 second cycle. Observation of changes in attitudes of students in cycle I 72 and cycle II 85.5. An increase of 13.5. Observation of changes in students' skills in cycle I 74 and cycle II 84. An increase of 10. Completion of learning outcomes in cycle I reached 36% and cycle II 89%. An increase of 53%. Based on these results, it can be concluded that the application of the guided inquiry learning model can improve learning outcomes in Mathematics in fifth grade students of Lawanggintung I Elementary School Bogor. In addition, this learning model can increase the sense of conscientiousness, cooperation, and responsibility of students in the learning process.